Status of Agri-Tourism Business in Central Luzon, Philippines: Basis for Development Plan - Esguerra, Imee De Guzman (Journal of Business on Hospitality and Tourism, 2020)
This study's main objective is to describe farmers' profile that venture into agri-tourism business, analyze the status of their business operation, determine the best practices and problems encountered by agri-tourism businesses in Central Luzon, which served as basis in crafting a development plan. The descriptive research method using a purposive sampling technique was employed in selecting the target respondents who were surveyed and interviewed using two separate sets of modified survey questionnaires. Agritourism businesses were accessible, family-run farms, affiliated with tourism and agriculture-related organizations, and compliant with required facilities and safety measures. Visitors were from all walks of life and came from within and outside the country. Classes, seminars, workshop, and tours were their top service offerings. Trust and confidence, referral system, hands-on operation, and strict financial monitoring were the identified best practices. At the same time, labour shortage, being still a niche market, price fluctuation, seasonality of farm products and services, insufficient staff skills, and significant capital requirements were the problems in running agri-tourism farms.